If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + -3 = 6 + -1(y + 11) Reorder the terms: -3 + -2y = 6 + -1(y + 11) Reorder the terms: -3 + -2y = 6 + -1(11 + y) -3 + -2y = 6 + (11 * -1 + y * -1) -3 + -2y = 6 + (-11 + -1y) Combine like terms: 6 + -11 = -5 -3 + -2y = -5 + -1y Solving -3 + -2y = -5 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. -3 + -2y + y = -5 + -1y + y Combine like terms: -2y + y = -1y -3 + -1y = -5 + -1y + y Combine like terms: -1y + y = 0 -3 + -1y = -5 + 0 -3 + -1y = -5 Add '3' to each side of the equation. -3 + 3 + -1y = -5 + 3 Combine like terms: -3 + 3 = 0 0 + -1y = -5 + 3 -1y = -5 + 3 Combine like terms: -5 + 3 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2
| .028x+3x=.34x | | 5(v-5)=7v-35 | | 7x/-7=4 | | -17=3(x+6)-8x | | 5v+19=2(v+8) | | 2/5x=-4/3 | | -9(v+1)=9v-45 | | x-576/576 | | h=.5wd | | x^3-9x*2-58x=228 | | 23x+13y=-3 | | d/hw=1/2 | | -11m+2m=14-68 | | d/2=hw | | -2/7x=-3/1 | | (9x^6)(-8x^9)(8x^7)= | | 10=-2w+8(w+5) | | d=.5hw | | 2t+12= | | 2/3*64-10 | | 1/8x-3/85/2x-17 | | -49=17t-10t | | (y-2)=-4x+4 | | -5=8(x-4)-5x | | (-3a)(2a)(-4a)= | | x+8=x^2+4x-7 | | 8v+2(v+2)=-36 | | -5+13=5b-8-4b | | c=.5mv | | c=1/2mv | | -4=6x+2(-4x) | | 2.5x+6y=480 |